The statement ~ (p↔ ~q) is
equivalent to p ↔ q
equivalent to ~ p ↔q
a tautology
a tautology
Consider :
Statement − I : (p ∧ ~ q) ∧ (~ p ∧ q) is a fallacy.
Statement − II : (p → q) ↔ (~ q → ~ p) is a tautology.
Statement -I is True; Statement -II is True; Statement-II is a correct explanation for Statement-I
Statement - I is True; Statement -II is true; Statement-II is not a correct explanation for Statement-I
Statement -I is True; Statement -II is False.
Statement -I is True; Statement -II is False.
The negation of the statement “If I become a teacher, then I will open a school” is
I will become a teacher and I will not open a school
Either I will not become a teacher or I will not open a school
Neither I will become a teacher nor I will open a school
Neither I will become a teacher nor I will open a school
Consider the following statements
P: Suman is brilliant
Q: Suman is rich
R: Suman is honest. The negation of the statement ì Suman is brilliant and dishonest if and only if Suman is richî can be ex- pressed as
~ P ^ (Q ↔ ~ R)
~ (Q ↔ (P ^ ~R)
~ Q ↔ ~ P ^ R
~ Q ↔ ~ P ^ R
Let S be a non empty subset of R. Consider the
following statement:
P: There is a rational number x∈S such that x > 0.
Which of the following statements is the negation of the statement P?
There is a rational number x∈S such that x ≤ 0.
There is no rational number x∈ S such that x≤0.
Every rational number x∈S satisfies x ≤ 0.
Every rational number x∈S satisfies x ≤ 0.
The following statement
(p → q ) → [(~p → q) → q] is
a fallacy
a tautology
equivalent to ~ p → q
equivalent to ~ p → q
Statement 1: ~ (p ↔ ~ q) is equivalent to p ↔ q
Statement 2 : ~ (p ↔ ~ q) is a tautology
Statement–1 is true, Statement–2 is true, Statement–2 is a correct explanation for statement–1
Statement–1 is true, Statement–2 is true; Statement–2 is not a correct explanation for statement–1.
Statement–1 is true, statement–2 is false.
Statement–1 is true, statement–2 is false.